Enteric multiplex PCR panels: A new diagnostic tool for amoebic liver abscess?. (July 2017) - Weitzel, T.; Cabrera, J.; Rosas, R.; Noriega, L.M.; Schiappacasse, G.; Vollrath, V.; Porte, L.
Abstract: Invasive amoebiasis is a life-threatening infection requiring immediate detection and treatment. However, diagnosis is challenging because conventional methods such as light microscopy and serology are unreliable. Molecular techniques are therefore considered the new diagnostic reference standard, but most of the developed assays are research tools and not widely available. Recently commercial multiplex PCR panels have been introduced which permit the simultaneous detection of multiple enteric pathogens including Entamoeba histolytica in stool samples. Our report demonstrates for the first time that these new assays might also serve as a rapid tool to diagnose amoebic liver abscess in patients with cystic focal liver lesions.